Screening and isolation of arsenic tolerant Rhizobacteria from arsenic contaminated areas of Bangladesh - Taher, AM; Quadir, QF; Hossen, MZ; Nazneen, T; Rahman, A (Progressive Agriculture, 2019)
An experiment was carried out to collect and isolate arsenic (As) tolerant rhizobacteria from As contaminated areas of Faridpur district. A total of 32 root samples of 17 plant species were collected from six locations of Bhanga and Nagarkanda upazila. From the plant roots, 16 rhizobacterial isolates were separated and their pure cultures were prepared. The collected rhizobacterial isolates were then characterized for morphological and biochemical traits. Among the bacterial isolates four were gram negative and 12 were gram positive. About 12 bacterial isolates had catalase producing capacity and the remaining three were negative to catalase test. Four bacterial isolates gave the positive HCN test. These bacterial isolates were grown on Pikovskays media to determine their phosphorus (P) solubilizing capacity. Four bacterial isolates had P solubilizing capacity and their Phosphorus Solubilizing Index (PSI) ranged between 3.00 and 4.66. However, isolate FB4 gave the highest P solubilization (4.66 PSI). For the evaluation of As tolerance, nutrient agar medium was prepared with different concentrations of As ranging from 30 to 600 ppm and the bacterial isolates were allowed to grow on the As contaminated medium for 36 hours. Isolate FB9 and FB4 showed maximum tolerance against As upto 600 ppm. Hence, these two isolates, both collected from Bhanga upazila and from wild brinjal species (Solanum capsicoides). Further research is needed to assess their effect on As dynamics at the rhizosphere, selection of suitable plant species for bacterial association and their potentials for field applications. Progressive Agriculture, Vol. 30, Suppl. 1: 17-25, 2019